Cultural Inheritance of Joged Pingitan Dance in Pengosekan, Ubud - Agus Made Wira Hadi Kusuma; Gusti Ayu Erma Yunita Dewi; Gusti Ayu Ratih Candra Giri; Ni Putu Putri Ditha Sumaridewi Oka; Ni Putu Candra Dewi Cahyanti; Ni Luh Putu Winda Sari Maharani K. A.; Ni Wayan Somawati (Institut Seni Indonesia Denpasar, 2023)
This study discusses the existence of Joged Pingitan dance in Banjar Pengosekan, Mas Village, Ubud, Bali. Joged Pingitan dance is included in the sacred dance which is believed to have strong religious and magical values by the people of Pengosekan Costumary Village. The religious value possessed by Joged Pingitan dance can be seen from its function as a wali/sacred dance to accompany the ceremony. This study raises three main issues, namely the history of Joged Pingitan dance, the functions of Joged Pingitan dance, and the values contained therein and the inheritance of Joged Pingitan dance in the globalization era. The purpose of this research is to answer all the problem formulations and dig deeper about Joged Pingitan dance. The method used is descriptive qualitative method with data collection techniques using observation and interview techniques. The results of this study explained that Joged Pingitan dance in Banjar Pengosekan is still preserved today, has the main function of being an accompaniment and complement during religious ceremonies and contains many values such as aesthetic values which are is the value of beauty, religious value, educational value, and social value.